Alterations in 'inflammatory' pathways in the rat prefrontal cortex as early biological predictors of the long-term negative consequences of exposure to stress early in life. (February 2021) - Lopizzo, Nicola; Mazzelli, Monica; Zonca, Valentina; Begni, Veronica; D'Aprile, Ilari; Cattane, Nadia; Pariante, Carmine M.; Riva, Marco A.; Cattaneo, Annamaria
Highlights: PNS affects the long-term modulation of pathways involved in inflammation and in stress response. PNS induces the most significant effects during adolescence. Gene expression alterations related to inflammation, stress response and metabolism. We suggest that high risk' adolescents may benefit from early strategies to prevent the onset of pathological outcomes. Abstract: Early life stress, especially when experienced during the first period of life, affects the brain developmental trajectories leading to an enhanced vulnerability for stress-related psychiatric disorders later in life. Although both clinical and preclinical studies clearly support this association, the biological pathways deregulated by such exposure, and the effects in shaping the neurodevelopmental trajectories, have so far been poorly investigated. By using the prenatal stress (PNS) model, a well-established rat model of early life stress, we performed transcriptomic analyses in the prefrontal cortex of rats exposed or not to PNS and sacrificed at different postnatal days (PNDs 21, 40, 62). We first investigated the long-lasting mechanisms and pathways affected in the PFC. We have decided to focus on the prefrontal cortex because we have previously shown that this brain region is highly sensitive to PNS exposure. We found that adult animals exposed to PNS show alterations in 389 genes, mainly involved in stress and inflammatory signalling. We then wanted to establish whether PNS exposure could also affect the neurodevelopmental trajectories in order to identify the most critical temporal window. We found that PNS rats show the most significant changes during adolescence (between PND 40 versus PND 21), with alterations of several pathways related to stress, inflammation and metabolism, which were maintained until adulthood.